Lectures in higher education: A 22-year systematic review (Journal of Applied Learning and Teaching, 2025)
Large-scale lectures alongside sandstone buildings are two of the most romanticised facets of higher education. While the Latin root to lecture means ‘to read’ (lectus is the past participle of legere), its practice has evolved with technology. Using a systematic review methodology leveraging a clear search strategy, screening and PRISMA reporting for articles between 2000-2022, this study curates knowledge on the contemporary lecture to provide a clear evidence base for future educators to draw upon in curriculum and learning design. Using Braun and Clarke (2006)’s thematic analysis of 296 papers on lectures, we identified six key theme areas: defence and critiques, examination of types of lectures, pedagogical adaptions, use of supports, student motivations and influences, and comparative evaluations of lecture-based instruction. We identify conflation and explore the clarity of the university lecture. Importantly, we identify that as the face-to-face lecture decreases in popularity as a research subject, it increases in online and recorded lectures are being observed. While longer-scale analysis is needed to understand the impact of this evolution on student engagement, attendance, and learning, it is evident that conflation of the types of lectures is making this kind of analysis difficult. We offer a clear typology of lectures to support future researchers and practitioners to be consistent in the application of lecture-based instructional pedagogy.